Black Blade - Lustbader, Eric 1946- (Grafton, 1992)
In New York City a chain of inhuman murders begins ... In V\feshington a high-level plot is hatched to bring the economic colossus of Japan to its knees... In Tokyo a deadly power struggle is under way within the shadowy organization known as the Black Blade Society. As Wolf Matheson, Chief of Special Homicide, begins his investigation into the chain of New York murders, he comes in contact with a mysterious force of unimaginable power. Blessed or cursed with the uncanny ability to track down killers, he is plunged into a terrifying spiral of betrayal, lust and evil. Then Wolf meets Chika, the beautiful Japanese woman who will become either his saviour or his murderer. Together, as lovers and perhaps enemies, they join in a desperate search that will unleash mystical forces, madness and violence.